Is Neck Dissection Associated with an Increased Risk of Postoperative Stroke?. (August 2017) - Cramer, John D.; Patel, Urjeet A.; Maas, Matthew B.; Samant, Sandeep; Smith, Stephanie Shintani
Objective: Prior studies have reported widely disparate rates of postoperative stroke, with conflicting analyses of whether neck dissection is an independent risk factor. Study Design: Cohort study. Setting: American College of Surgeons National Surgical Quality Improvement Program from 2005 to 2013. Subjects and Methods: We compared the 30-day rate of postoperative stroke between patients undergoing complete or modified radical neck dissection and a control cohort composed of those undergoing resections in the oral cavity, oropharynx, larynx, or hypopharynx without neck dissection. Propensity scores and paired statistics were used to compare the groups while adjusting for relevant covariates. Results: We identified 9697 patients, including 5827 with neck dissection and 3870 without neck dissection. In the full cohort, the rate of postoperative stroke was greater with neck dissection than without it (0.31% vs 0.11%, P = .052), although the relationship was attenuated by propensity score matching to adjust for comorbidities (0.30% vs 0.13%, P = .18). Among patients with ≥2 risk factors for carotid artery stenosis, neck dissection was associated with an increased rate of postoperative stroke (2.68% with bilateral neck dissection, 0.41% with unilateral neck dissection, and 0.24% without neck dissection, P = .04). The incidence of stroke was strongly associated with 30-day mortality (7.4% vs 0.2%, P < .001). Conclusions: Stroke is a rare but highly morbid complication after head and neck surgery. Compared with other head and neck surgery, neck dissection in patients at risk for carotid artery stenosis is associated with an increased risk of postoperative stroke.